The views of general practitioners and practice nurses towards the barriers and facilitators of proactive, internet-based chlamydia screening for reaching young heterosexual men - Lorimer, Karen (BioMed Central, 2014)
BACKGROUND: Chlamydia trachomatis is a common bacterial sexually transmitted infection (STI), which disproportionately affects young people under 25 years. Commonly, more women are offered screening than men. This study obtained the views of general practitioners and practice nurses towards Internet-based screening and assessed levels of support for the development of proactive screening targeting young heterosexual men via the Internet. METHODS: Semi-structured telephone interviews with 10 general practitioners and 8 practice nurses, across Central Scotland. Topics covered: experience of screening heterosexual men for chlamydia, views on the use of the Internet as a way to reach young men for chlamydia screening, beliefs about the potential barriers and facilitators to Internet-based screening. Transcripts from audio recordings were analysed with Framework Analysis, using QSR NVivo10. RESULTS: Experiences of chlamydia screening were almost exclusively with women, driven by the nature of consultations and ease of raising sexual health issues with female patients; few practice nurses reported seeing men during consultations. All participants spoke in favour of Internet-based screening for young men. Participants reported ease of access and convenience as potential facilitators of an Internet-based approach but anonymity and confidentiality could be potential barriers and facilitators to the success of an Internet approach to screening. Concerns over practical issues as well as those pertaining to gender and socio-cultural issues were raised. CONCLUSIONS: Awareness of key barriers and facilitators, such as confidentiality, practicality and socio-cultural influences, will inform the development of an Internet-based approach to screening. However, this approach may have its limits in terms of being able to tackle wider social and cultural barriers, along with shifts in young people’s and health professionals’ attitudes towards screening. Nevertheless, employing innovative efforts as part of a multi-faceted approach is required to ensure effective interventions reach the policy agenda.